‘Landscape of Memory’: the case of Bronze and Iron Age Armenia - Avetisyan, Hayk; Gnuni, Artak; Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
Historical memory lies at the basis of identity of each society and predetermines the value system of that society. However historical memory is not purely an abstract category: the existence of it is justified only in a certain landscape, the separate elements of which, as landmarks, create the so called ‘landscape of memory’. This ‘embodied’ sphere of memory, which is expressed both in geographical units as well as in spiritual and material values predominates especially in traditional societies, which in contradiction to industrial and post-industrial future-oriented societies, are wholly oriented to the memory – to the past and ancestors. Thus, the ‘landscape of memory’ is a stratified database of memory under which a concrete space becomes sacred and the time – cyclic.